Performance of a hard X‐ray split‐and‐delay optical system with a wavefront division. (6th December 2017) - Hirano, Takashi; Osaka, Taito; Morioka, Yuki; Sano, Yasuhisa; Inubushi, Yuichi; Togashi, Tadashi; Inoue, Ichiro; Matsuyama, Satoshi; Tono, Kensuke; Robert, Aymeric; Hastings, Jerome B.; Yamauchi, Kazuto; et al.
Abstract : The performance of a hard X‐ray split‐and‐delay optical system with a wavefront division scheme has been investigated at SACLA. Abstract : The performance of a hard X‐ray split‐and‐delay optical (SDO) system with a wavefront division scheme was investigated at the hard X‐ray free‐electron laser facility SACLA. For the wavefront division, beam splitters made of edge‐polished perfect Si(220) crystals were employed. We characterized the beam properties of the SDO system, and investigated its capabilities for beam manipulation and diagnostics. First, it was confirmed that shot‐to‐shot non‐invasive diagnostics of pulse energies for both branches in the SDO system was feasible. Second, nearly ideal and identical focal profiles for both branches were obtained with a spot size of ∼1.5 µm in full width at half‐maximum. Third, a spatial overlap of the two focused beams with a sub‐µm accuracy was achieved by fine tuning of the SDO system. Finally, a reliable tunability of the delay time between two pulses was confirmed. The time interval was measured with an X‐ray streak camera by changing the path length of the variable‐delay branch. Errors from the fitted line were evaluated to be as small as ±0.4 ps over a time range of 60 ps.